2002
DOI: 10.1007/s00425-001-0716-y
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of 1- O -sinapoylglucose:malate sinapoyltransferase in Arabidopsis thaliana

Abstract: The serine carboxypeptidase-like protein 1- O-sinapoylglucose:malate sinapoyltransferase (SMT) catalyzes the transfer of the sinapoyl moiety of 1- O-sinapoylglucose to malate in the formation of sinapoylmalate in some members of the Brassicaceae. Rabbit polyclonal monospecific antibodies were raised against the recombinant SMT produced in Escherichia coli from the corresponding Arabidopsis thaliana (L.) Heynh. cDNA. Immunoblot analysis of protein from different Arabidopsis tissues showed that the SMT is produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 48 publications
3
43
0
1
Order By: Relevance
“…The identification of signal peptides via SignalP in 49 of the 51 SCPL proteins is consistent with experimental work showing that CPY and SMT are transported to the vacuole (Marshall, 1972;Stevens et al, 1982;Sharma and Strack, 1985;Valls et al, 1987;Hause et al, 2002). The SignalP results are also supported by the fact that the signal peptide sequence removed from the mature form of SMT (Lehfeldt et al, 2000) is accurately predicted by the algorithm.…”
Section: Arabidopsis Scpl Proteins Have Structural Features In Commonsupporting
confidence: 82%
“…The identification of signal peptides via SignalP in 49 of the 51 SCPL proteins is consistent with experimental work showing that CPY and SMT are transported to the vacuole (Marshall, 1972;Stevens et al, 1982;Sharma and Strack, 1985;Valls et al, 1987;Hause et al, 2002). The SignalP results are also supported by the fact that the signal peptide sequence removed from the mature form of SMT (Lehfeldt et al, 2000) is accurately predicted by the algorithm.…”
Section: Arabidopsis Scpl Proteins Have Structural Features In Commonsupporting
confidence: 82%
“…In recent years, it has been suggested that monolignols can be glucosylated and stored as such in the vacuoles (Miao and Liu, 2010), a feature they share with some phenylpropanoid precursors (Figure 2). For example, sinapoyl glucose and sinapoyl malate are present in the vacuoles of Arabidopsis cells (Hause et al, 2002). However, the bulk of the monolignols will be exported to the cell wall for oxidation by peroxidase and/or laccase whereupon the resulting radicals cross-couple nonstereospecifically to form the lignin polymer Vanholme et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, phenylpropanoic acids in Arabidopsis thaliana are often derivatized to glucose esters (e.g., sinapoyl glucose). Since sinapoylglucose:malate sinapoyltransferase, catalyzing the conversion of sinapoyl glucose to sinapoyl malate, is present in the vacuole (Sharma and Strack, 1985;Hause et al, 2002), and because monolignol glucosides can be transported through the tonoplast via ATP binding cassette-like transporters (Miao and Liu, 2010), sinapoyl glucose and the monolignol glucosides are likely stored in the vacuole. A vacuolar localization of coniferin and other monolignol glucosides has been speculated (Leinhos and Savidge, 1993;Dharmawardhana et al, 1995) but has not yet been unambiguously proven (Kaneda et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the predicted signal peptide suggests targeting of the protein to the secretory pathway or, more likely, to the vacuole. Avenacins are known to accumulate in the vacuoles of oat root epidermal cells (Mylona et al, 2008), and the only SCPL acyltransferase that has been localized to date (the Arabidopsis 1-O-sinapoylglucose:malate sinapoyltransferase) is found in the vacuole (Hause et al, 2002).…”
Section: The Scpl1 Protein Is Posttranslationally Processed and Is LImentioning
confidence: 99%
“…However, not all SCPL proteins undergo such processing (Hause et al, 2002;Stehle et al, 2006). Comparison of the amino acid sequences of oat SCPL1 with those of characterized SCP and SCPL proteins (some of which undergo cleavage and some of which do not) reveals that SCPL1 has an extended linker region typical of SCPL proteins that are cleaved into two subunits ( Figure 7A).…”
Section: The Scpl1 Protein Is Posttranslationally Processed and Is LImentioning
confidence: 99%